Doula Support in The Success of a Normal Delivery - I Nyoman Hariyasa Sanjaya; Cokorda Istri Mirayani Pemayun; Made Diah Vendita Sakuntari; Ni Wayan Dewi Purwanti; Ni Putu Nining Gianni; Ni Luh Made Diah Mas Cahyani Putri; Ni Komang Anik Pirgantari; Ni Luh Md Dwi Laxmi Satriani; Firsta Sesarina Mintariani; Anak Agung Wahyu Putri Agustini; Ketut Widyani Astuti (Indonesian Journal of Perinatology, 2021)
Introduction: Many mothers who give birth are less interested in giving birth normally because of the intense labor pain. Actually it can be overcome by doula assistance. The doula's presence provides emotional support during the preparation for childbirth, and the doula provides physical support by accompanying to overcome hunger, thirst, and pain. The aim of this study was to determine the effect of doulas assistance on the success of delivery. Methods: This study is a descriptive observational study with a cross-sectional design conducted at a private hospital in Bali in the period January 2020 to January 2021. The inclusion criteria in this study were all pregnant women with gestational age 34 to 40 weeks who were willing to undergo the study. While the exclusion criteria in this study were pregnant women who experienced complications during childbirth and pregnant women with incomplete clinical and demographic data. All of the data was analyzed descriptively by using SPSS 25 and was presented by frequency. Result: This study managed to collect as many as 100 pregnant women who will give birth with the help of a doula. It was found that as many as 60 people (60%) gave birth vaginally. Then followed by 31 people (31%) who underwent a Cesarean section with the help of a doula. There were also 5 people (5%) and 4 people (4%) who underwent epidural delivery and vacuum extraction with the help of a doula. Conclusion: Doula assistance during labor can increase the confidence of the mother who will give birth and support the success of normal delivery.